A totally implantable venous access port associated with bloodstream infection caused by Mycobacterium fortuitum: A case report. Issue 29 (July 2018) - YE, Huifen; Zeng, Junshao; Qin, Wenzhou; Yang, Zhao; Yang, Ling; Wu, Zhitong; Du, Guinian
Abstract: Rationale: Rapidly growing mycobacteria (RGM) are well-known causative agents of human infections, particularly in immunocompromised hosts. However, Mycobacterium fortuitum, a predominant organism, in catheter-associated infections, has rarely been documented in totally implantable venous access port (TVIAP)-associated bloodstream infections. Patient concerns: A 25-year-old woman with breast cancer presented to hospital with repeated fever for several days. The patient first refused to remove the TVIAP in her body, and had a relapse of M. fortuitum bacteraemia four months later. Diagnoses: Bacteria isolated from patient's blood and TVIAP were identified as M. fortuitum by Matrix-assisted laser desorption/ionization-time of flight spectrometry and bacterial 16s rDNA sequencing. The patient was diagnosed as a TVIAP-associated bloodstream infection. Interventions: The TVIAP was eventually surgically removed, and M. fortuitum was found to have localized on the tip of the catheter. The patient was treated by anti-infection therapy. Outcomes: The patient was treated with 4 weeks of intravenous amikacin and levofloxacin followed by 4 weeks of oral levofloxacin. No episodes of fever occurred during the follow-up to date. Lessons: RGM infections remain a challenging issue for TIVAPs. Accurate species identification, timely intravascular catheter removal and appropriate antibiotic therapy are recommended to ensure successful outcomes.